PEARAN POLA ASUH DAN PENGGUNAAN GADGET TERHADAP INTERAKSI SOSIAL ANAK DI LINGKUNGAN DUPAK MASIGIT GANG III SURABAYA - Elsofi Alintya; Miftakhul Jannah; Risandi Mardanis Putri; Diyas Age Larasati (Jurnal Inovasi Penelitian, 2022)
Children are people who are in the process of growing up. Child growth is a transformation process as children learn to climb to a larger level from several points of view: movement, thinking, feeling, and interacting with both living things and objects in the child's living area. The growth of children certainly cannot be separated from the education of parents who have responsibility for children's learning, namely by guiding and training children through learning with pictures, adjustments, advice and attention on things that are useful for children. Childhood is also the time for them to learn to socialize with the surrounding area to build self-confidence in children. Due to the continued advancement of technology, most parents share gadgets with children, gadgets have bad and good effects for children. The purpose of this research is to master the position of parenting and the use of gadgets for social interaction in children in the Dupak Masigit Gang III area, Surabaya. The subjects of this research are children who have used gadgets, parents who already have children and residents who have a significant function in children's growth. The instrument used in this research is the scale of social interaction in children and the position of parenting for children. The result of this research is that children have the assumption that gadgets have benefits in them and have positive and negative consequences. Not only that, children also want to formulate that gadgets are a primary need, so it can be concluded that the position of parenting for children is indeed needed in children's daily lives.